A scenario on plastic shopping bags: Issues continue ... / Arba' at Hassan and Maimunah Sokro - Hassan, Arba' at; Sokro, Maimunah (2004)
Human beings were using tools made from stones in their early civilization. The tools were then changed to metal: heavy, bulky, and inconvenience. The later material, called plastic, was invented as early in 1930s by Americans, British, and Germans. Plastic is widely used today in many applications (from the cheapest to the most expensive, and the simplest to the most sophisticated). The plastic bag: polyethylene (polythene) (HDPE and LDPE), other important type of plastic, is cheap, flexible, durable, convenience, and chemically resistant. However, their use and disposal contribute negative impact to environment and reinforce the perception of a wasteful society. Plastic bags as litter, create pollution problems to human beings, animals, and environment. The issues have become major concerns around the world. Suggestions to minimize the impacts of using plastic bags including the 6R approach, applying other alternative, educating people (With environmental knowledge, awareness, skills) and applying citizenship actions effectively.